Avaliação da toxicidade do azocorante Acid Red 114 antes e após processo de biodegradação por meio de um consórcio de microorganismos - Corroqué, Nádia Aline [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Textile industries have contributed to the contamination of water bodies by disposing their effluents into the environment. These industries use a wide variety of dyes in dyeing processes, among them, the azo dyes. These azo dyes due to their molecular characteristics of difficult removal or degradation and their extensive use, are considered highly detrimental to the environment. The dye Acid Red 114, is included in the class of azo dyes, and it is the chemical agent target of this study. This study is proposed to investigate the possibility of degradation by microorganisms isolated from the sludge of a textile industry and evaluate the toxicity of the Acid Red 114 dye and by-products generated in its biodegradation. To evaluate the toxicity of this dye parameters of genotoxicity and mutagenicity were considered. For the genotoxicity analysis, the comet assay in cultured human hepatoma (HepG2) was used. To evaluate the mutagenic potential, the micronucleus test (MN) in HepG2 cultured cells and Salmonella/microsome test were performed. Evidence of biodegradation was taken by physicochemical method of spectrophotometry UV-Vis and FTIR. According to the results, the Acid Red 114 dye showed to be genotoxic and mutagenic to HepG2 cells but not mutagenic to Salmonella typhimurium. The biodegraded generated by the bacteria Enterococcus faecalis and Alcaligenes faecalis was genotoxic and mutagenic to HepG2 cells, but not mutagenic to Salmonella/microsome test. The biodegraded generated by the bacterium Achromobacter nitridificans showed in HepG2 cells, genotoxic potential, but was not mutagenic to HepG2 or Salmonella/microsome test. These toxicity results showed that the use of this dye requires great caution, as it can have adverse action in living beings, including humans, either by direct contact to the dye (e.g. occupational via or use of confectioned products) or by the inadequate treatment of textile effluents or water treatments that use...

As indústrias têxteis têm contribuído para a contaminação dos corpos d’água, por descartar seus efluentes no meio ambiente. Essas indústrias utilizam uma grande diversidade de corantes em seus processos de tingimento, dentre eles, os azocorantes. Estes corantes azóicos, pela sua característica molecular de difícil remoção ou degradação, somado ao seu amplo uso, são considerados altamente detrimentais ao ambiente. O corante Acid Red 114, pertencente a classe dos azocorantes, é o agente químico alvo deste trabalho. Este estudo tem como proposta, investigar a possibilidade de degradação por microrganismos isolados do lodo de uma indústria têxtil e avaliar as toxicidades do corante Acid Red 114 e dos subprodutos gerados na sua biodegradação. Para avaliação da toxicidade deste corante, foram considerados os parâmetros de genotoxicidade e mutagenicidade. Para análise da genotoxicidade, foram utilizados o ensaio do cometa em cultura de hepatoma humano (HepG2). Para avaliar o potencial mutagênico, foram realizados os testes do micronúcleo (MN) em cultura de células HepG2 e o teste de Salmonella/microssoma. A comprovação da biodegradação foi feita por meio do método físico-químico de Espetrofotometria UV-Vis e FTIR. De acordo com os resultados obtidos, o corante Acid Red 114 mostrou-se genotóxico e também mutagênico para as células HepG2, mas não mutagênico para Salmonella typhimurium. O biodegradado gerado pelas bactérias Enterococcus faecalis e Alcaligenes faecalis foi genotóxico e mutagênico para a cultura celular HepG2, mas não foi mutagênico no teste com Salmonella/microssoma. O biodegradado gerado pela bactéria Achromobacter nitridificans apresentou, em células HepG2, potencial genotóxico, mas não foi mutagênico para HepG2 nem para o teste de Salmonella/microssoma. Estes resultados de toxicidade mostraram que o uso deste corante requer bastante cautela, pois ele pode ter ação adversa nos...
Keywords: Biodegradation; Biodegradação; Toxicidade - Testes; Corantes; Ensaio cometa; Corantes - Toxicologia; Toxicologia genética